Mirvetuximab Soravtansine in FRα-Positive, Platinum-Resistant Ovarian Cancer - Moore, Kathleen N; Angelergues, Antoine; Konecny, Gottfried E; García, Yolanda; Banerjee, Susana; Lorusso, Domenica; Lee, Jung-Yun; Moroney, John W; Colombo, Nicoletta; Roszak, Andrzej; Tromp, Jacqueline; Myers, Tashanna; et al. (The New England journal of medicine, 2023)
BACKGROUND: Mirvetuximab soravtansine-gynx (MIRV), a first-in-class antibody-drug conjugate targeting folate receptor α (FRα), is approved for the treatment of platinum-resistant ovarian cancer in the United States. METHODS: We conducted a phase 3, global, confirmatory, open-label, randomized, controlled trial to compare the efficacy and safety of MIRV with the investigator's choice of chemotherapy in the treatment of platinum-resistant, high-grade serous ovarian cancer. Participants who had previously received one to three lines of therapy and had high FRα tumor expression (≥75% of cells with ≥2+ staining intensity) were randomly assigned in a 1:1 ratio to receive MIRV (6 mg per kilogram of adjusted ideal body weight every 3 weeks) or chemotherapy (paclitaxel, pegylated liposomal doxorubicin, or topotecan). The primary end point was investigator-assessed progression-free survival; key secondary analytic end points included objective response, overall survival, and participant-reported outcomes. RESULTS: A total of 453 participants underwent randomization; 227 were assigned to the MIRV group and 226 to the chemotherapy group. The median progression-free survival was 5.62 months (95% confidence interval [CI], 4.34 to 5.95) with MIRV and 3.98 months (95% CI, 2.86 to 4.47) with chemotherapy (P<0.001). An objective response occurred in 42.3% of the participants in the MIRV group and in 15.9% of those in the chemotherapy group (odds ratio, 3.81; 95% CI, 2.44 to 5.94; P<0.001). Overall survival was significantly longer with MIRV than with chemotherapy (median, 16.46 months vs. 12.75 months; hazard ratio for death, 0.67; 95% CI, 0.50 to 0.89; P = 0.005). During the treatment period, fewer adverse events of grade 3 or higher occurred with MIRV than with chemotherapy (41.7% vs. 54.1%), as did serious adverse events of any grade (23.9% vs. 32.9%) and events leading to discontinuation (9.2% vs. 15.9%). CONCLUSIONS: Among participants with platinum-resistant, FRα-positive ovarian cancer, treatment with MIRV showed a significant benefit over chemotherapy with respect to progression-free and overall survival and objective response. (Funded by ImmunoGen; MIRASOL ClinicalTrials.gov number, NCT04209855.).
Keywords: Platinum Compounds; Humans; Female; nádory vaječníků; Ovarian Neoplasms; lidé; humanizované monoklonální protilátky; chemorezistence; Maytansine; sloučeniny platiny; folátový receptor 1; Carcinoma, Ovarian Epithelial; epiteliální ovariální karcinom; Antibodies, Monoclonal, Humanized; ženské pohlaví; imunokonjugáty; Folate Receptor 1; Immunoconjugates; maytansin; Drug Resistance, Neoplasm